2017
DOI: 10.1038/s41598-017-03538-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating angiopoietin-like 8 (ANGPTL8) is a marker of liver steatosis and is negatively regulated by Prader-Willi Syndrome

Abstract: ANGPTL8 is a liver-derived protein related to insulin-sensitivity. Its relationship with obesity and liver function in Prader-Willi syndrome (PWS) is unknown. The present study investigated circulating ANGPTL8 in PWS and controls with common obesity, assessing its association to liver steatosis. For this purpose, 20 obese PWS and 20 controls matched for body mass index (BMI), sex and age underwent analysis of ANGPTL8 levels, glucose and lipid metabolism. Liver function tests and degree of liver steatosis by ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…It is possible that the inconsistency may be associated with the origins of obesity. It is reported that circulating ANGPTL8 concentrations are different in people with obesity depending on the origins of obesity [ 46 ] which may be linked to body composition, basal metabolic rate, or metabolic outcomes [ 47 ]. To avoid a confounding effect, we adjusted for age and BMI in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the inconsistency may be associated with the origins of obesity. It is reported that circulating ANGPTL8 concentrations are different in people with obesity depending on the origins of obesity [ 46 ] which may be linked to body composition, basal metabolic rate, or metabolic outcomes [ 47 ]. To avoid a confounding effect, we adjusted for age and BMI in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid a confounding effect, we adjusted for age and BMI in this study. Circulating ANGPTL8 concentrations are elevated in patients with non-alcoholic fatty liver disease [ 48 ] and liver steatosis [ 46 ]. It is also reported that there is a positive association between circulating ANGPTL8 and serum Hs-CRP [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Body measurements. All subjects underwent body measurements wearing light underwear, in fasting conditions after voiding as described previously 25,26 . Weight and height were measured to the nearest 0.1 kg and 0.1 cm, respectively, using standard methods.…”
Section: Methodsmentioning
confidence: 99%
“…Waist circumference (WC) was measured midway between the lowest rib and the top of the iliac crest after gentle expiration; hip measurements were taken at the greatest circumference around the nates. FM and FFM were determined by bioelectrical impedance analysis (BIA model 101/S Akern, Florence, Italy) as described previously 26 . According to the vectorial analysis, patients with fluid overload were excluded to minimize errors in estimating FM and FFM.…”
Section: Methodsmentioning
confidence: 99%
“…124 Prader-Willi syndrome patients exhibit unique body composition in comparison to obese controls 125,122 with higher insulin sensitivity alluding to alternative pathogenic pathways. 126,127 Wilson's disease A wide spectrum of histological findings can be found in Wilson's disease, ranging from a chronic porto-lobular hepatitis with no steatosis to a steatohepatitis-like picture, similar to that seen in alcoholic liver disease. Special stains for copper may help point towards the diagnosis, but the distribution of copper may be patchy and not always be present.…”
Section: Key Pointmentioning
confidence: 99%